Design of an active a 5- bit digitally programmable phase shifter for hybrid antenna beamformers - Esteban Eraso, Uxua; Sánchez-Azqueta, Carlos; Aldea Chagoyen, Concepción; Celma Pueyo, Santiago (Jornada de Jóvenes Investigadores del I3A, 2022)
This paper presents the design of a new 5-bit digitally programmable phase shifter using CMOS technology of 65 nm, for its use in hybrid antenna beamformers opperating at the part of the K-band destinated to SATCOM communications. Simulation results are compared with previously reported alternatives.